ANALISIS CRASHING TIME MENGGUNAKAN MS-PROJECT DALAM PELAKSANAAN PEKERJAAN PADA PROYEK PENINGKATAN JALAN (Jurnal Spesialis Teknik Sipil (JSpTS), 2019)
The Sangkulirang-Bontang road improvement project is in the form of delays on the seventhweek of December amounting to 6.21%. The cause of the delay in the execution of work wasthe problem of asphalt work and thermoplast road marking equipment. This research isintended to obtain optimal solutions in order to catch up on project delays. There are twoalternatives that can be assessed, namely the first addition to the time of workimplementation using the amount of equipment available, and the second by increasing theamount of equipment used. It turned out that the first alternative cost was Rp. 18,349,500.24with a period of 17 days. The second alternative is the implementation cost of Rp.36,699,234.86 but with a processing time of 9 days. Because the first alternative is cheaperwith time still permissible, the first alternative is chosen. In order to catch up on work delays,planning and scheduling are obtained and the acceleration of the duration of the projectcompletion is 1 day from the initial project planning of 59.0%. And in terms of costs there isa difference in the contract value of Rp.5,565,986,000.00 with a total cost of work of Rp.4,647,256,026.19 or Rp. 505,998,154.81 amounting to 0.165%Keywords: planning and scheduling project, delays, crashing time, road improvement